Neural correlates underlying state anxiety alterations following sleep deprivation: insights from frontal alpha asymmetry and phase-amplitude coupling - Hao, Chao; Xie, Feiyang; Bu, Naifeng (Frontiers in Psychology, 2025)
IntroductionElevated anxiety stands as a prominent adverse consequence of sleep deprivation. However, the resting-state neural correlates underlying the alterations in state anxiety following sleep deprivation remain to be further examined. The present study delved into the impact of sleep deprivation on state anxiety and its underlying neural correlates.MethodsWith 20 participants, we recorded their resting-state electroencephalogram activities and assessed their state anxiety using the State Anxiety Inventory Scale during both normal sleep and 24-hour sleep deprivation sessions.ResultsResults show that sleep deprivation induced a significant increase in state anxiety. Additionally, there was a general elevation in resting-state electroencephalographic power, with notable increases observed in the delta, theta, alpha, and beta frequency bands, as well as the delta-beta phase-amplitude coupling. Meanwhile, the frontal alpha asymmetry presented a left lateralization after sleep deprivation. Furthermore, the heightened beta2 power and delta-beta2 phase-amplitude coupling exhibited a significant positive correlation with increased state anxiety after sleep deprivation. The left-lateralized frontal alpha asymmetry was linked to the enhancement in state anxiety following sleep deprivation.DiscussionThe present study provided the resting-state electroencephalographic evidence that accounts for the magnified state anxiety after sleep loss.